Therapeutic Effect of Neuromuscular Joint Facilitation on Hemiplegia Patients with Cerebral Infarction - LIN Shaoying; YE Li; CHEN Zhenghong (康复学报)
ObjectiveTo explore the therapeutic effect of neuromuscular joint faciclitation (NJF) on the upper extremity muscle tone, upper limb and hand motor function and turn over and transfer ability in hemiplegic patients with cerebral infarction.MethodsA total of 136 patients with cerebral infarction treated in the Department of Neurology of the First Affiliated Hospital of Sun Yat-sen University from August 2017 to January 2019 were divided into control group and experimental group according to whether the treatment includes the NJF technique, with 70 and 66 cases in each group, respectively. Both groups received conventional drug therapy for stroke. The control group received upper limb rehabilitation therapy on the basis of conventional treatment, including functional electrical stimulation, passive joint movement training and transfer ability training, each training was 20 minutes a time, once a day, five days a week, continuous training for 10 days. The experimental group received NJF technical training on the basis of the control group, including upper limb extension-adduction-internal rotation mode, upper limb flexion-abduction-external rotation mode, upper limb flexion-adduction-external rotation mode and upper limb extension-abduction-internal rotation mode, 60 minutes a time, of which NJF technical training lasted for 20 minutes, the treatment content in the control group was shortened to 40 minutes a time, once a day, five days a week, continuous training for 10 days. Before and after the treatment, modified Ashworth spasticity scale (MAS) was used to assess the muscle tension of the upper limbs; Brunnstrom staging was used to assess the motor function of the affected upper limbs and hand; the amount of help needed when transferring was used to assess the ability of turning over (including turning over to the healthy side and turning over to the affected side).Results(1) MAS score of upper limb and Brunnstrom score of upper limb and hand: compared with before treatment, the difference in MAS score and Brunnstrom score of the upper limb of the two groups after treatment were statistically significant (P<0.05) , and the difference of Brunnstrom score of hand in the experimental group after treatment was statistically significant (P<0.05). Compared with the control group, the improvement rate of MAS grading, upper limb and hand Brunstrom staging in the experimental group were significantly higher, and the differences were statistically significant (P<0.05). (2) Turn over and transfer ability: Compared with before treatment, the difference of score of turning to the healthy side of both groups after treatment was statistically significant (P<0.05) , while the difference of turning to the affected side of the control group after treatment was statistically significant (P <0.05). Compared with the control group, the improvement rate of turning to the healthy side of the experimental group was significantly higher, and the difference was statistically significant (P<0.05).ConclusionNJF technology can reduce the high muscle tone of upper extremity, improve the upper extremity, hand movement ability and the turn over and transfer ability of hemiplegia patients with cerebral infarction.